Intravascular Glomus Tumor of the Forearm Causing Chronic Pain and Focal Tenderness - Sang Ki Lee; Dae Geon Song; Won Sik Choy (Case Reports in Orthopedics)
Introduction. A glomus tumor is a benign vascular tumor derived from glomus cells and occurs mainly in the subcutaneous layer of the subungual or digital pulp. Extradigital glomus tumors have been reported within the palm, wrist, forearm, foot, bone, stomach, colon, cervix, and mesentery. Glomus tumors can originate from the intraosseous, intramuscular, periosteal, intravascular, and intraneural layers. However, a glomus tumor originating from the intravascular layer of the forearm is a rare condition. Case Report. A 44-year-old woman had a 7-year history of chronic pain and focal tenderness of the forearm. No hypersensitivity or sensory alterations were observed. Contrast magnetic resonance imaging (MRI) showed a mass measuring 5 × 3 × 2 mm leading to a vein. Surgical excision was performed, and the tumor was completely resected. Finding of gross examination revealed a dark-red, well-defined soft tissue tumor, and histologic examination confirmed that the mass was a glomus tumor. The patient’s symptoms were completely resolved postoperatively. Conclusion. Intravascular glomus tumors rarely occur in the forearm; therefore, a thorough physical exam, comprehensive medical history, in-depth imaging, and early surgical excision upon clinical suspicion may be helpful to prevent a delayed or incorrect diagnosis.